(3bUGFO aj eOM GdfHi Udi Gddg Ydjg hSdes - (3eMeO Hf SYjO Hf MeGO Hf YHO Gddg GdUfgGLj GdHhUjQj GdeUQj, TQa GdOjf, CHh YHO Gddg , (B696 (3g` s ((3YdjNGf Hf eUWai s)
(3ChdgG (B:s
(3bGd GdTjN CHh YHO Gddg eMeO Hf SYjO GdHhUjQi SHH EfTGFi gPg GdbUjOI GdeHGQcI Cfi cfJ bO CUGHfi NdW aGdL CHWd fUai aacQJ Cf CfTF bUjOI ai eOM GdfHi Udi Gddg Ydjg hSde hGSJTaY Hg Edi Gddg s
(3BNQgG (B:s
(3ef CfRdJ ajg Cef gh bGfJ PGc GdPi LeY GdcJGH GdeMceG hGdBd hGdUMH GdcQGe aEfge TgH EP Gddjd GdMhGOK CXdeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH (B4107) s
Keywords: (3GdCOHs